Моя жизнь: опыт автобиографии (Л. Д. Троцкий) - Троцкий Лев Давидович
Экземпляры: Селтинская районная библиотека (к/х) (20200610) / Инвентарный номер: 161421 / Авт.знак: Т 76 / ГРНТИ: 17 / ББК: 84(2=411.2)